Small Toxic Molecule Detection and Elimination Using Molecularly Imprinted Polymers (MIPs) - Min Seok Kang; Jin-Ho Lee; Ki Su Kim (Biosensors, 2025)
Molecularly imprinted polymers (MIPs) provide selective, robust, and cost-effective platforms for the detection and removal of small toxic molecules in environmental, food, and biomedical contexts. This review offers a comprehensive overview of recent advancements in MIP-based systems, emphasizing critical design factors such as template selection, functional monomers, polymerization methods, and binding kinetics. The impact of these parameters on improving sensitivity, selectivity, and reusability is thoroughly examined. Additionally, current advantages, limitations, and enduring challenges are addressed. By highlighting emerging strategies and interdisciplinary innovations, this work aims to guide the development of more efficient and sustainable technologies for small-molecule toxin detection and remediation.